THE EFFECT OF THE RECOMMENDATIONS OF THE COMMUNITY SUPERVISOR (PK) OF BAPAS GRADE 1 CIREBON ON THE JUDGE'S DECISION IN THE TRIAL OF CHILDREN FACING THE LAW (ABH) - Irma Maulida; Alya Dwi Putri; Ari Rafsanjani; Geisya Safana Camila; Lulu Abeliyani; Marsha Nurfadillah (Jurnal Abdisci, 2025)
Abstract Introduction. Indonesia's juvenile criminal justice system is designed to provide maximum protection for children's rights. Law No. 11/2012 on the Juvenile Criminal Justice System (UU SPPA) emphasizes the importance of the restorative justice approach as the main principle in handling cases of Children Against the Law (ABH). One of the supporting elements for the application of this principle is the recommendations prepared by the Community Supervisor (PK) in the Community Research Report (LITMAS). These recommendations provide a comprehens. Aims. The picture of the social, psychological, and family and community conditions in which children grow up, which then become material for the judge's consideration in determining the appropriate treatment. However, in court practice, PK recommendations are not always used as the basis for sentencing. There are disparities in how judges respond and accommodate the assessment results. Based on this, the author aims to analyze the influence of PK recommendations on judges' decisions in ABH trials. This research uses a normative juridical approach with mixed methods (qualitative and quantitative). Method. Data was collected from a documentation study of 11 judges' decisions heard in early 2025 until March 24, 2025, and through analysis of the accompanying LITMAS results. Results. This research shows that in 8 of the 11 cases, the judges aligned with the LITMAS recommendations (72.7%). Meanwhile, in the other 3 cases, the judges did not fully accommodate the recommendations of the PK, with a percentage of 27.3%. Conculsion. This finding shows that, although the PK recommendations significantly influence the majority of decisions, there is still room to improve the consistency and quality of their implementation. Increasing the capacity of PKs, standardizing the preparation of LITMAS, and strengthening communication between PKs and judges are some solutions that enhance the implementation of restorative justice.